A Study of the Effect of Teachers’ Behavior on Students’ Academic Achievement at Secondary Schools Level - Sajjad Anwar; Muhammad Hameed Nawaz (Elementary Education Online, 2023)
The present research was designed to explore the effect of teachers’ behaviour on students’ academic achievement at secondary school level. It was descriptive research based on survey design and was conducted in Gujranwala division. The data was collect from 1221 students of the 10th class who were selected by applying simple random sampling technique via self-developed questionnaire. The collected data was arranged, coded, and entered into computer for analysis. Data was analyzed by applying inferential statistics with the help of SPSS (version 20) software. The result shows that there is significant difference in the effect of teachers’ behaviours on the academic achievement of students. The teachers who always adopted directive behaviour in the class, their students learn more because majority of them performed “excellent” in exam which indicates high academic achievement of students. The teachers who always adopted authoritative behaviour in the class, their students learn moderately because majority of them performed “good” in exam which indicates moderate academic achievement of students. The teachers who always adopted aggressive behaviour in the class, their students learn poor because majority of them performed “average” in exam which indicates poor academic achievement of students, and the teachers he/she who always adopted tolerance behaviour in the class, their students learn moderately because majority of them performed “very good” in exam which indicates very good academic achievement of students.